RETRACTED: Priority Algorithm Based Coordinated Voltage Control for Distribution System with Distributed Wind Generators. (2015) - Chidanandappa, R.; Ananthapadmanabha, T.; Vishwanath, S.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of scientific committee of SMART GRID Technologies 2015. The authors have plagiarized part of a paper that had already appeared in PRZEGLĄD ELEKTROTECHNICZNY (Electrical Review), 6 (2012) 304 - 312, http://pe.org.pl/abstract_pl.php?nid=6091 . One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.